The experience of modernization of mills of wet wire drawing for the metal wire cord - A. V. Demidov; I. A. Muraveiko (Литьë и металлургия)
There is a tendency in recent years to use by the world’s leading manufacturers of tires metal wires of small diameter (0,175– 0,20 mm) with higher strength, which requires the use of increased total number of extracts on wet drawing. The possibility of increasing the compression can be limited not only by the ductility of the processed metal, but also by the design of the existing drawing mills, in particular, by the insufficient total passport kinematic drawing and, as a consequence, to the excessive sliding of the wire relative to the drawing washers. Results of modernization of mills of different types including increase in number of transitions of drawing to 28 with decrease in private and increase in total passport extracts at the expense of installation of additional drawing washers of small diameter and additional reducing dies are considered. The results show that the positive effect of the improvement of some technological parameters can be offset by the deterioration of other factors. It is shown that the mills with three pairs of drawing cones have more opportunities for this modernization than similar mills, but with two pairs of cones. The criterion of estimation of influence of sizes of drawing washers on plastic properties of a wire for a metal cord based on experience of operation of mills with different construction of kinematics is offered.